2011
DOI: 10.1136/jnnp-2011-300511
|View full text |Cite
|
Sign up to set email alerts
|

MRI preclinical detection and asymptomatic course of a progressive multifocal leucoencephalopathy (PML) under natalizumab therapy: Figure 1

Abstract: Early detection of progressive multifocal leucoencephalopathy (PML) in the setting of natalizumab therapy currently is performed by rapid evaluation of new symptoms occurring in treated patients. The role of MR scanning has not been investigated but holds promise since MR detection is highly sensitive for PML lesions. The authors report a case of presymptomatic PML of the posterior fossa detected by MR scans. Immediate suspension of natalizumab and plasma exchanges resulted in a rapid decline of natalizumab se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 18 publications
4
54
0
2
Order By: Relevance
“…We are not aware of the specific context and outcome of the 4 other N-PML cases, which were diagnosed and treated in other centers. The reported cases emphasize that 1) N-PML can have a long presymptomatic course while still being clearly detectable with MRI, 2) N-PML can have a benign outcome provided it is diagnosed and treated early, 3) a clinically symptomatic N-PML may be a further advanced infection with a poorer prognosis, and 4) periodic brain MRI scans, particularly in high-risk situations, are likely to provide earlier detection of N-PML 4 and better outcomes. Written informed consent was obtained from all 4 patients.…”
Section: The Earlier the Smaller The Better For Natalizumab-associamentioning
confidence: 99%
See 2 more Smart Citations
“…We are not aware of the specific context and outcome of the 4 other N-PML cases, which were diagnosed and treated in other centers. The reported cases emphasize that 1) N-PML can have a long presymptomatic course while still being clearly detectable with MRI, 2) N-PML can have a benign outcome provided it is diagnosed and treated early, 3) a clinically symptomatic N-PML may be a further advanced infection with a poorer prognosis, and 4) periodic brain MRI scans, particularly in high-risk situations, are likely to provide earlier detection of N-PML 4 and better outcomes. Written informed consent was obtained from all 4 patients.…”
Section: The Earlier the Smaller The Better For Natalizumab-associamentioning
confidence: 99%
“…2 In patients with prior JCV infection detected by serum anti-JCV antibodies, 3 duration of therapy and prior use of immunosuppressants (IS) increase the risk of N-PML. The clinical outcome of patients with MS who developed N-PML was highly variable, ranging from asymptomatic case 4 to varying degrees of neurologic disability or even death. 5 It was also observed in real-life setting that the earlier N-PML was diagnosed and treated, the better was the clinical outcome.…”
Section: The Earlier the Smaller The Better For Natalizumab-associamentioning
confidence: 99%
See 1 more Smart Citation
“…Natalizumab treatment requires a 1-h infusion plus a 1-h observation period every month [18,19,70], giving a total burden of at least 48 h over 2 years. For early detection of PML, it has been suggested that MRI analysis may be needed as often as every 6 months in patients who are positive for anti-JCV antibodies, in addition to regular assessment by medical and nursing staff and cerebrospinal fluid analysis [68,76].…”
Section: Natalizumabmentioning
confidence: 99%
“…19,20 Most interesting, compared with other PML cohorts, contrast enhancement can be observed quite frequently in natalizumab-associated PML (NTZ PML), occurring in approximately 30% of all patients at diagnosis, and can be the leading radiologic sign in asymptomatic patients. [22][23][24] Substantial evidence indicates that FLAIR is the most sensitive sequence for detecting PML. 22 DWI is known to be highly sensitive for depicting acute demyelination but can also aid in the differentiation of acute PML lesions from chronic and subacute demyelinating MS lesions.…”
Section: Diagnosing Pmlmentioning
confidence: 99%